Evaluating The Performance Of Unconfined Compressive Strength Of Trong Clay Stabilized With Granite Sludge - Che Mamat, R.; Ramli, A.; Mat Yazid, M. R. (Journal of Engineering and Technology (JET), 2017)
This research paper aims to evaluate the potential usability of granite sludge as a stabilizer of Trong clay based on compressive strength. There are eight mixture combination between the clay and the stabilizer with ratios of 0, 1, 2, 3, 4, 5, 6 and 7 wt% granite sludge. The value of shear strength is obtained through unconfined compression tests performed in the laboratory. The research found that the performance of unconfined compressive strength increased with the percentage of stabilizer. Sample S7 which contains 7% granite sludge is found to yield the highest unconfined compressive strength of 585kN/m2. This is 187% higher than unstrengthened sample. This study found that, the compressive strength improved with increased granite sludge content in the soil mixture.